(untitled) (Academicia Globe: Inderscience Research, 2023)
By today’s fast-paced era, the globalization process in any field is becoming one of the most important factors in the life of society. Developed countries consider the place of youth education in the development of society and Human Development important. Therefore, they also pay special attention to the quality of Education. In particular, the signing of an agreement on the participation of Uzbekistan in the research of PISA and PIRLS will pave the way for a radical reform of the educational system of the Republic of Uzbekistan and will contribute to the development of intellectual activity of the younger generation, their competence and creativity in education. In the course of reading the article below, you can learn more about one of these assessment programs –PIRLS.